Ways to create information masking system of the Interior Troops units combat and day-to-day activities in protecting key infrastructure under conditions of territorial defense - Varakuta, V. P.; Pehakhin І. А.; Pistriak, P. V.; Razinkina О. H. (Honor and Law, 2019)
The analysis of damasking features of combat and day-to-day activities of the Interior Troops units in protecting key infrastructure is given. The ways to create information masking system of the Interior Troops units combat and day-to-day activities are detained.